Dichloromethane extracts of propolis protect cell from oxygen-glucose deprivation-induced oxidative stress via reducing apoptosis - Li-Ping Sun (Food & Nutrition Research, 2016)
Background: Bee propolis, a mixture of the secretion from bee tongue gland and wax gland, was collected from the tree bud and barked by bees. The components were rich in terpenes, phenolics, and flavonoids, and had anti-cancer, anti-bacterial, anti-inflammatory, hepatoprotective, and neuroprotection abilities. However, the potential anti-oxidative stress of propolis was not well documented. This study aimed to study the protective effect of propolis on high-incident nonfatal diseases, such as stroke and cerebral infarction caused by ischemia. Objective: Oxidative stress caused by acute stroke results in inflammation and injury followed by cell damage and apoptosis. Clarification of the anti-oxidative stress effect of propolis may contribute to stroke prevention and damage reduction. Design: Propolis was separated and purified into 70% ethanol and dichloromethane extracts systematically. The fraction three (Fr.3) of dichloromethane was further separated into pinocembrin, pinobanksin, pinobanksin-3-acetate, chrysin, and galangin by chromatography. Compounds extracted from propolis were tested for cell-protection effects in an oxygen-glucose deprivation (OGD) N2a cell model. MTT assay, oxidative stress markers measurement, flow cytometry, and QPCR were used to evaluate cell viability and apoptosis. Results: All compounds, especially pinocembrin and galangin, enhanced cell viability in OGD-treated N2a cells. In addition, anti-oxidative enzymes were elevated and cellular Ca2+ was reduced. They also had extreme anti-apoptosis effects by up-regulating the expression of Bcl-2 mRNA and down-regulating caspase-3 and Bax expression. Taken together, propolis had anti-oxidative effects on stress and protected cells from damage. Conclusion: The anti-oxidative effect of propolis can be applied to daily food supplements and may benefit stroke patients.